THE EFFECT OF PERCEPTION AND PROFIT SHARING ON THE DECISION TO BECOME A CUSTOMER AT BANK BNI SYARIAH MERANGIN REGENCY - Ahmadi, Ahmadi (Dinasti Publisher, 2019)
This study aims to analyze the effect of perceptions on the decision to choose partially, the share of the decision to choose partially, and the perception and profit sharing of the decision to choose simultaneously. The design of this study is quantitative using the survey method. The population of this study is the customer of BNI Syariah bank in Merangin Regency. The sample size in this study was determined through the Slovin formula with e value = 10%, so that a sample of 95 people was obtained. This study uses multiple linear regression analysis techniques. SPSS 21.00 analysis aid. The results of this study indicate that perceptions and profit sharing have a positive and significant effect on the decision to become a customer at Bank BNI Syariah Merangin Regency. There are still other factors that influence the decision to choose apart from the two variables of public perception and profit sharing.